The role of on-farm trials in the evaluation of composite technologies: The case of alley farming in southern Nigeria - Atta-Krah, A.N.; Francis, P.A. (Elsevier, 1987)
Discusses the role of on-farm research in the evaluation of alley farming. Presents ILCA's experience in on-farm research and alley farming at the Humid Zone Programme and discusses the different stages of on farm-trials ,viz, exploratory, intermediate and pilot project. Looks in to the evaluation of the pilot project and examines tree utilisation, farmer perceptions, adoption & diffusion of technology, and relationship between on-farm and on-station work.